Effect of ZnO addition on the purity and densification of forsterite ceramic - Tan C.Y.; Tan Y.M.; Ramesh S.; Yap B.K. (Institute of Physics Publishing, 2023)
Densification; Engineers; Mechanical properties; Milling (machining); Olivine; Solid state reactions; Zinc oxide; Forsterite ceramics; Forsterite powder; Lower sintering temperatures; Maximum relative density; Sintering additives; Sintering process; Solid state reaction method; Two-step sintering; Sintering